Notes on recollection of Primula sherriffiae W.W.Sm. after a gap of 74 years from India with comments on the typification of the name - Mao, A.a.; Krishna, Gopal; Jalal, Jeewan Singh (Phytotaxa, 2022)
Primula sherriffiae W.W.Sm. has been collected after a gap of 74 years from Indo-Myanmar border, near Poi village, Manipur. It was last collected from India for the same state of Manipur in 1948. The species is very unique in having longest corolla tube (c. 10 cm long) so far, in all known Primula spp. Comments have been made on the typification of the name and possible threats and its conservation status are also discussed.